Hydroxychloroquine use in a community-based cohort of patients with systemic lupus erythematosus - Schmajuk, Gabriela (2010)
BACKGROUND: In recent years hydroxychloroquine (HCQ) has emerged as a key therapy in systemic lupus erythematosus (SLE). We determined the rates of HCQ use in a diverse, community-based cohort of patients with SLE and identified predictors of current HCQ use. METHODS: Patients were participants in the University of California San Francisco (UCSF) Lupus Outcomes Study (LOS), an ongoing longitudinal study of patients with confirmed SLE. We examined the prevalence of HCQ use per person-year and compared baseline characteristics of users and non-users, including demographic, socioeconomic, clinical, and health-system use variables. Multiple logistic regression with generalized estimating equations was used to evaluate predictors of HCQ use. RESULTS: Eight hundred and eighty one patients contributed 3095person-years of data over 4 interview cycles. The prevalence of HCQ use was 55 per 100 person-years and was constant throughout the observation period. In multivariate models, the odds of HCQ use were nearly doubled among patients receiving their SLE care from a rheumatologist compared to those identifying generalists or nephrologists as their primary sources of SLE care. In addition, patients with shorter disease duration were more likely to use HCQ, even after adjusting for age and other covariates. CONCLUSIONS: In this community-based cohort of patients, HCQ use was suboptimal. Physician specialty and disease duration were the strongest predictors of HCQ use. Patients who are not using HCQ, those with longer disease duration, and those who see non-rheumatologists for their SLE care should be targeted for quality improvement.